2007
DOI: 10.1210/jc.2006-1757
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Sexual and Reproductive Outcomes in Women with Classical Forms of Congenital Adrenal Hyperplasia

Abstract: Objectives:The objectives of the study were 2-fold: 1) a detailed description of sexual and reproductive outcomes in adult women with congenital adrenal hyperplasia (CAH) of different phenotypic severity at birth; and 2) comparisons of these outcomes among CAH subtypes and between CAH women and non-CAH control women.Design: This was a cross-sectional study using a face-to-face interview, a written questionnaire, the Female Sexual Function Index, and a gynecological examination. Patients: Patients included 35 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
117
4
12

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(139 citation statements)
references
References 26 publications
6
117
4
12
Order By: Relevance
“…Sexual function is reduced in women with CAH compared to controls, and it is lowest in women with the most severe degrees of virilization. In a study from France [85], 81% of women with CAH reported pain during vaginal penetration, and half were noted to have moderate or severe stenosis of their introitus. The live-birth rate in classic salt-wasting forms has been reported to be 0% to 10%, in simple virilizing forms 33% to 50%, and in non-classic forms 63% to 90% [84].…”
Section: Reproductive Outcome—womenmentioning
confidence: 99%
“…Sexual function is reduced in women with CAH compared to controls, and it is lowest in women with the most severe degrees of virilization. In a study from France [85], 81% of women with CAH reported pain during vaginal penetration, and half were noted to have moderate or severe stenosis of their introitus. The live-birth rate in classic salt-wasting forms has been reported to be 0% to 10%, in simple virilizing forms 33% to 50%, and in non-classic forms 63% to 90% [84].…”
Section: Reproductive Outcome—womenmentioning
confidence: 99%
“…In Turner syndrome, uterine hypoplasia is reported [12], and achievement of normal uterine growth during hormone replacement therapy in adolescence and early adulthood is likewise difficult. A suboptimal uterine development may contribute to the lower fertility rates seen in CAH females [13, 14], and may be associated with a higher prevalence of miscarriage and premature birth. …”
Section: Discussionmentioning
confidence: 99%
“…Infertility is inextricably related to self-esteem and psychosocial adjustment. The anatomic concerns related to women with classic CAH such as pain with vaginal penetration are generally not germane for women with NCAH [83]. As surgical, medical, and psychological treatments have improved, more women with classic and NCAH have successfully completed pregnancies and given birth [84].…”
Section: Psychosocial Considerations and Quality Of Lifementioning
confidence: 99%